Tallinna XI Graafikatriennaal. - Keskküla, Ando; Komissarov, Eha; Rotermann's Salt Storage Arts Centre, Tallinn; Tallin Art Hall, Tallinn; City Gallery, Tallinn; Vaal Gallery, Tallinn (Tallinn : Association of Estonian Printmakers, 1998)
Kuusing, Kai ; Lotz, Sylvia ; Nevin, Pete ; Sietins, Guntars ; Gotleyb, Leonardo ; Juan, Andrea ; Mandrile, Cecilia ; Crothers, Wayne ; Etienne, Luc ; Harem, Habib ; Sinte, Claude ; Pomeranz, Noeli ; Sabral, Armando ; Kazandjiev, Tzvetan ; Allik, Peeter ; Eelma, Onne ; Gordin, Igor ; Heam*agi, Inga ; Jöekalda, Virge ; Kalm, Anu ; Kann, Voldemar ; Keerend, Avo ; Liiva, Silvi ; Marks, Ulle ; Meel, Raul ; Mäetamm, Marko ; Nukke, Mall ; Ojaver, Jüri ; Ootsing, enno ; Raud, Piret ; Ruben, Lembe ; Siib, Liina ; Smagar, Piret ; Tolli, Vive ; Tonts, Annika ; Viik, Urmas ; Vint, Aili ; Castro Cobos, Manuel ; Boerendans, Henriette ; Mizrahi, Anita ; Shereshevsky, Hadass ; Balasubramaniam, A. ; Barker, Dale ; Bloor, Chris ; Colverson, Ian ; Ganter, Jo ; Swallow, Wendy ; Sykes, Sandy ; Hrafnkelsdóttir, Svava ; Jónsdóttir, Ragnheidur ; Sigurdardóttir, Gréta Ósk ; Bracchitta, Sandro ; Carraro, Luisa ; Paladino, Mimmo ; Hamano, Toshihiro ; Hayakawa, Junko ; Kimura, Hideki ; Kiyono, Koichi ; Kuroyanagi, Masataka ; Nagashima, Mitsuru ; Obata, Etsuko ; Okada, Marie ; Sakurai, Sadao ; Yamazaki, Naohide ; Yoshizumi, Toshio ; Armstrong, David ; Chiba, Taiga ; Dempster, Alec ; Dugas, Karen ; Fox, Nancy ; Ingram, Liz ; Jule, Walter ; Kim, Seung-Yeon ; Sang-Gon, Chung ; Sachinis, Xenophon ; Bzeskas, Egmontas ; Ceponis, Ramunas ; Daniliauskaite, Viktorija ; Dauksaité - Guobiené, Irena Terese ; Dubaushiené, Lida ; Grigaliunas, Kestutis ; Kalinauskas, Vytautas ; Kepezinskas, Rimvydas ; Krasauskaite, Aiste Jurga ; Markevicius, Tomas ; Plikionyté, Joana Danute ; Ramunaite, Aiste ; Rudinskas, Egidijus ; Salciute, Laisvydé ; Vaigeltaite, Roberta ; Vasiliunas, Kestutis ; Abele, Dina ; Blumbergs, Ilmars ; Heinrihsone, Helena ; Kalnacs, Andrejs ; Krollis, Gunars ; Ozola, Arta ; etc.
geboortedatum per kunstenaar
Engels & Ests
The Tenth Tallinn Graphic Triennial, Tallinn, 18.09 - 18.10.1998, Rotermann's Salt Storage Arts Centre, Tallinn ; Tallin Art Hall, Tallinn, Gallery of the Tallinn Art Hall, Tallinn ; City Gallery, Tallinn ; Vaal Gallery, Tallinn
kunstcatalogus